Typification of fourteen names of twelve recognized taxa in Leucas R. Br. (Lamiaceae) and one new combination (Bangladesh Journal of Plant Taxonomy, 2016)
Eight binomials of six recognized species of Indian Leucas R. Br. are lectotypified, namely, Leucas beddomei (Hook. f.) Sunojk. & P. Mathew, L. diffusa Benth., L. helianthemifolia Desf., L. nepetifolia Benth., L. pilosa Benth., L. pilosa Benth. var. pubescens Benth., L. ternifolia Desf. and L. vestita Benth. Two recognized taxa are neotypified, namely, L. angularis Benth. and L. lanata Benth. var. candida Haines. L. lanata Benth. var. candida Haines is raised to species rank as L. candida (Haines) R.Kr. Singh. L. pilosa Benth. is added to the flora of India. Additionally the following four recognized endemic species of Leucas of Myanmar are also lectotypified, Leucas collettii Prain, L. helferi Hook. f., L. ovata Benth. and L. teres Benth.Bangladesh J. Plant Taxon. 23(1): 33-43, 2016 (June)